Innovative Gravity-Fed Filtration System to Improve Coastal Community Water Quality - Ronny, Ronny; Hasan, Zulfikar Ali; Telan, Albina Bare (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Efforts to meet clean water needs, especially for drinking water, depend on the condition of groundwater that is healthy and sufficiently available. Filtration is the process of separating particles from a liquid by passing the liquid through a permeable material. This study examines the Gravity-Fed Filtering System with innovative Imhoff technology, combined with a Primary Treatment stage, to produce clearer and higher-quality water. The objective of this research is to assess the effectiveness of this system in reducing contamination levels in groundwater, including iron (Fe), manganese (Mn), total hardness (Ca and Mg), and organic compounds. The study employed an experimental method with a quantitative approach and used a One Group Pretest-Posttest design. The research was conducted in two locations: Barombong Village in Makassar and Pauwo Village in Gorontalo. Fifteen samples were randomly selected for analysis. The study began with preliminary observations and initial testing in March 2022, followed by the main research and prototype evaluation in 2023-2024. The results show that the system effectively reduced Fe, Mn, organic compounds, and total hardness levels. In Makassar, the highest reduction in Fe is 87.3% in sample 8, while in Gorontalo, the highest reduction is 93.3% in sample 8. The highest reduction in manganese (Mn) in Makassar is 63.3% in sample 1, and in Gorontalo, it is 62.1% in sample 1. The highest reduction in organic compounds in Makassar is 81.6% in sample 3, while the lowest reduction in total hardness in Makassar is 77.1% in samples 4, 5, 6, and 10. In Gorontalo, the highest reduction in total hardness is 90.3% in samples 1, 2, and 3. Recommendations for the community, The use of gravity-fed filtering system technology as one of the media used to reduce iron and manganese concentrations is considered quite good, but for similar research to be carried out, modifications should be made to the media specifically starting with the size, shape and other variables that support it so that it is more effective in reducing pollutant concentrations.